Analisis Prilaku Pembelian Perumahan Terhadap Keputusan Konsumen Pada Perumahan Bumi Marina Mas PT. Mega Bumi Erlangga Di Surabaya - Bambang Sukma Alam (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2018)
The development of the property sector in Kotamadya Surabaya today shows considerable progress rapidly both in terms of the provision of facilities / infrastructure and in terms of the number of people working in the property sector. Marketing strategic concept Keegan (1996: 5) said the concept of marketing strategy is a major development in the history of marketing thinking, change the marketing focus of the customers or products to customers within the context of the broader external environment. The concept of companies marketing should be able to understand its consumers as a whole to progress and develop.Understanding consumers absolute treated in the era of information and increasingly fierce competition today. But to understand those consumers completely is not easy, because the consumer is very complex. The complexity of the consumer caused by the human factor that is their human needs and desires are unlimited, in addition influenced by external and internal conditions that result directly on their behavior.In general how consumers behave in the purchase is influenced by external and internal factors. The internal factor is a factor that is in the consumers themselves which include: motivation, learning, personality and self-concept and attitude. External factors include: culture and sub-cultures, social classes, social groups and reference groups and families. Consumer behavior are discussed in this study is the internal behavior of consumers housing Bumi Marina Emas. The analysis model is the model of Multiple Linear Regression analysis, the reason is the independent variable is composed of several variables and suspected if variable - the independent variable increases, the dependent variable increases.Keywords: Customer Behavior, Customer Decision